2007
DOI: 10.1111/j.1365-313x.2007.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of the plastidial glucose‐6‐phosphate/phosphate translocator inViciaseeds shifts cellular differentiation and promotes protein storage

Abstract: SummaryThe glucose-6-phosphate/phosphate translocator (GPT) acts as an importer of carbon into the plastid. Despite the potential importance of GPT for storage in crop seeds, its regulatory role in biosynthetic pathways that are active during seed development is poorly understood. We have isolated GPT1 from Vicia narbonensis and studied its role in seed development using a transgenic approach based on the seed-specific legumin promoter LeB4. GPT1 is highly expressed in vegetative sink tissues, flowers and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 64 publications
(86 reference statements)
4
38
0
1
Order By: Relevance
“…6 B and C), and represented one of the highest EST counts of all carbohydrate-related genes of oil palm mesocarp. Interestingly, antisense inhibition of a GPT transporter in Vicia seeds altered carbon partitioning and promoted protein storage at the expense of carbohydrates (25). ESTs for the phosphoenolpyruvate (PEP) transporter PPT1 were 3.7 times higher than in date palm and increased fourfold during oil palm ripening (Figs.…”
Section: Increased Transcripts For Specific Enzymes and Transporters mentioning
confidence: 99%
“…6 B and C), and represented one of the highest EST counts of all carbohydrate-related genes of oil palm mesocarp. Interestingly, antisense inhibition of a GPT transporter in Vicia seeds altered carbon partitioning and promoted protein storage at the expense of carbohydrates (25). ESTs for the phosphoenolpyruvate (PEP) transporter PPT1 were 3.7 times higher than in date palm and increased fourfold during oil palm ripening (Figs.…”
Section: Increased Transcripts For Specific Enzymes and Transporters mentioning
confidence: 99%
“…A detailed analysis of heterozygous GPT1/gpt1 plants revealed that the development of both the female and the male gpt1 gametophyte are impaired. Two more recent investigations showed that GPT1 is also involved in embryo development and seed maturation (Rolletschek et al, 2007;Andriotis et al, 2010). A reduction of GPT1 expression of about 50% in seeds of Vicia narbonensis by an antisense approach with a seed-specific promoter led to a shift in assimilate partitioning from starch/ lipids into storage proteins, indicating that GPT1 exerts a significant control on seed filling and maturation (Rolletschek et al, 2007).…”
Section: Reverse Genetics: a Powerful Toolmentioning
confidence: 99%
“…Two more recent investigations showed that GPT1 is also involved in embryo development and seed maturation (Rolletschek et al, 2007;Andriotis et al, 2010). A reduction of GPT1 expression of about 50% in seeds of Vicia narbonensis by an antisense approach with a seed-specific promoter led to a shift in assimilate partitioning from starch/ lipids into storage proteins, indicating that GPT1 exerts a significant control on seed filling and maturation (Rolletschek et al, 2007). A reduction of more than 80% of GPT1 expression in Arabidopsis seeds is lethal because embryo development stops at the globular stage (Andriotis et al, 2010).…”
Section: Reverse Genetics: a Powerful Toolmentioning
confidence: 99%
“…Accumulating evidence in all dicotyledonous plant species studied so far (e.g. Arabidopsis, broad bean [Vicia faba], and potato [Solanum tuberosum]) points to Glc-6-P as the preferred translocated hexose phosphate and the Glc-6-P/phosphate antiporter GPT1 as the active translocator (Kammerer et al, 1998;Geigenberger et al, 2004;Niewiadomski et al, 2005;Rolletschek et al, 2007;Zhang et al, 2008). This is further supported by the fact that the loss of plastidial PGI1 activity impacts starch accumulation only in autotrophic Arabidopsis cells (Yu et al, 2000;Tsai et al, 2009), while mutations affecting plastidial PGM1 result in a low-starch phenotype in both autotrophic and heterotrophic tissues (Caspar et al, 1985).…”
mentioning
confidence: 99%